Impact of coexistent preserved ratio impaired spirometry on the survival of patients with lung cancer: Analysis of data from the Korean Association for Lung Cancer Registry. Issue 18 (1st August 2021) - Heo, I. Re; Kim, Ho Cheol; Lee, Seung Jun; Yoo, Jung‐Wan; Ju, Sunmi; Jeong, Yi Yeong; Lee, Jong Deog; Cho, Yu Ji; Jeong, Jong Hwan; Heo, Manbong; Jung, Seung Woo; Kim, Tae Hoon
Abstract: Background: Preserved ratio impaired spirometry (PRISm) is a common spirometric pattern that is associated with respiratory symptoms and higher mortality rates. However, the relationship between lung cancer and PRISm remains unclear. This study investigated the clinical characteristics of lung cancer patients with PRISm and the potential role of PRISm as a prognostic factor. Methods: We retrospectively reviewed data collected from 2014 to 2015 in the Korean Association for Lung Cancer Registry. We classified all patients into three subgroups according to lung function as follows: normal lung function; PRISm (forced expiratory volume in 1 s [FEV1 ] < 80% predicted and FEV1 /forced vital capacity [FVC] ≥ 0.7); and chronic obstructive pulmonary disease (COPD; FEV1/FVC < 0.7). In non–small cell lung cancer (NSCLC) and small cell lung cancer (SCLC), the overall survival period was compared among the three subgroups. The prognostic factors were investigated using Cox regression analysis. Results: Of the 3763 patients, 38.6%, 40.1%, and 21.3% had normal lung function, COPD, and PRISm, respectively. Patients with PRISm had poorer overall survival than those with COPD or normal lung function in NSCLC and SCLC (Mantel–Cox log‐rank test, p  < 0.05). In the risk‐adjusted analysis, overall survival was independently associated with COPD (hazard ratio [HR] 1.209, p  = 0.027) and PRISm (HR 1.628, p  < 0.001) in NSCLC, but was only associated with PRISm (HR 1.629, p  = 0.004) in SCLC. Conclusions: PRISm is a significant pattern of lung function in patients with lung cancer. At the time of lung cancer diagnosis, pre‐existing PRISm should be considered a predictive factor of poor prognosis. Abstract : Thisretrospective analysis evaluated the prognostic role of the preserved ratioimpaired spirometry (PRISm). The patients with PRISm had shorter overallsurvival period than those with chronic obstructive pulmonary disease (COPD) ornormal lung function in both NSCLC and SCLC groups.